Is Intervertebral Cement Leakage a Risk Factor for New Adjacent Vertebral Collapse? - Churojana, Anchalee (Interv Neuroradiol, 2014)
This retrospective study evaluated the relationship between intervertebral cement leakage and new adjacent vertebral fracture and describes the different characteristics of cement leakage. Increased risk of new adjacent vertebral fracture (NF) has been reported to be a complication of cement leakage in vertebroplasty. In our observation, an incidental intervertebral cement leakage may occur during vertebroplasty but is commonly asymptomatic. The study focused on osteoporotic collapse patients who had percutaneous vertebroplasty (PV) between 2005 and 2007. We divided patients into leakage and non-leakage groups and compared the incidence of NF. Leakage characteristics were divided into three types: Type I intervertebral-extradiscal leakage, Type II intradiscal leakage and Type III combined leakage. Visual analog scale for pain and the Karnofsky Performance Status at 24 h, three months, six months and one year were compared between groups and types of leakages. Among 148 PVs (102 patients) there were 30 leakages (20.27%) and 21(14.19%) NFs. The incidence of NF did not significantly differ between leakage and non-leakage groups (P<0.05). Type II was the most common type of leakage (15/30). Reduction of average pain and improvement of Karnofsky Performance Status score did not differ between groups (P< 0.05). Type II had decreased pain score < type I and III at 24 h (P< 0.01), three months and six months (P< 0.1) but not at one year (P<0.10). Type II also had decreased pain score < non-leakage group only at 24 h (P<0.05). Intervertebral cement leakage is not an increased risk for NF, influenced outcomes of pain relief or improvement of physical function. Intradiscal leakage (Type II) is the most common characteristic of cement leakage and probably related to delayed pain relief.